2017
DOI: 10.1038/cddiscovery.2017.59
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB pathway link with ER stress-induced autophagy and apoptosis in cervical tumor cells

Abstract: Targeting endoplasmic reticulum (ER) stress is being investigated for its anticancer effect in various cancers, including cervical cancer. However, the molecular pathways whereby ER stress mediates cell death remain to be fully elucidated. In this study, we confirmed that ER stress triggered by compounds such as brefeldin A (BFA), tunicamycin (TM), and thapsigargin (TG) leads to the induction of the unfolded protein response (UPR) in cervical cancer cell lines, which is characterized by elevated levels of inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 39 publications
(37 reference statements)
3
32
0
Order By: Relevance
“…The link between NF-κB and autophagy in the current work might have been established in Cd group. Concordantly, Quinazolinediamine which is an NF-κB inhibitor had been proved to ameliorate both autophagy and apoptosis induced by brefeldin [31]. Agreeing with the results of this work the relation between Sildenafil and NF-κB, it had been proved that Roflumilast, a phosphodiesterase4 inhibitor, might mitigate cadmium-induced renal toxicity via modulation of NF-κB activation and induction of NQO1 in rats [3,28].…”
Section: Discussionsupporting
confidence: 56%
“…The link between NF-κB and autophagy in the current work might have been established in Cd group. Concordantly, Quinazolinediamine which is an NF-κB inhibitor had been proved to ameliorate both autophagy and apoptosis induced by brefeldin [31]. Agreeing with the results of this work the relation between Sildenafil and NF-κB, it had been proved that Roflumilast, a phosphodiesterase4 inhibitor, might mitigate cadmium-induced renal toxicity via modulation of NF-κB activation and induction of NQO1 in rats [3,28].…”
Section: Discussionsupporting
confidence: 56%
“…The results indicate the involvement of NF‐κB in HIF‐1 α activation for late generation Cell Line A. It has been reported that NF‐κB activation could be induced by ER stress or unfolded protein response . In this study, RNAseq analysis detected age‐correlated overexpression of the ER stress marker ATF4 in Cell Line A but not in Cell Line B ( p = 4.64 × 10 −17 ).…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, the cell surface localization of MT1‐MMP, rather than its proteolytic processing, was found to contribute to the ER stress induction process . In support, ER stress‐induced autophagy and apoptosis in cervical tumor cells was recently reported . Intriguingly, the biological significance of the transient ARP101‐mediated formation of MT1‐MMP dimers followed by the formation of MT1‐MMP tetramers at higher ARP101 concentrations remains unknown.…”
Section: Discussionmentioning
confidence: 92%